Polish Factor in the Policy of the Russian Power in Right-Bank Ukraine (the End of the Eighteenth Century – 1830s) - Bortnikov, Valerii; Bortnikova, Alla; Pavlikha, Nataliia (Український історичний журнал, 2020)
The purpose of the research is to clear up the forms of relations of the imperial center with the Polish elites on the territories acquired by Russia, to identify the peculiarities of the tsarist governments policy regarding their influence in Right-Bank Ukraine at the end of the eighteenth century – in the 1830s. Research methodology. A number of special historical research methods have been used in the article: comparative, procedural, political-legal, temporal, problem-chronological, content-analysis, prosopographic, hermeneutical, and others. Scientific novelty. The dynamics of solving "Polish issue" by the ruling upper circles headed by Emperors Paul I, Alexander I, and Nicholas I in the context of identifying specific institutional forms and means of integration of the Right-Bank territories into the Russian Empire have been clarified. Conclusions. It has been established, that, within the indicated chronological limits, the patterns of the Imperial centers relations with the Polish elites on the Right-Bank lands developed from a tolerant attitude towards the Polish influence on the social-political development of the region to a consistent policy of unification and depolonization of the annexed territories. During the reign of Paul I, the General Court, district-county and nobility courts were re-established on the territories joined after the partitions of the Polish-Lithuanian Commonwealth, and instead of marshals of the nobility, the positions of provincial and county marshals and cornets were introduced. It has been confirmed that All-Russian legal rules and the Lithuanian Statute co-existed on the Right-Bank territories at that time. Under Alexanders I reign the tolerant attitude to the Polish influence on the Right-Bank lands continued, which implied a combination of imperial unification policy with the recognition of regional peculiarities and historical identity of the annexed territories. It has been noted that fundamental changes in the "Polish issue" occurred during the reign of Nicholas I, after the revolutionary events in European countries and, first of all, the November uprising of 1830. It has been determined that from that time the policy of the Russian government regarding the Poles in the Right-Bank provinces was pursued in several directions: attracting the Polish nobility to the Russian elites by incorporating it into the social category of nobility and conferring appropriate rights and privileges; the repressions against Polish patriots; transferring the vast majority of minor-landed Polish gentry to taxable social categories; conducting judicial reform, under which town courts were liquidated and mandatory use of the Russian language was introduced in legal proceedings; limiting the conditions of existence of the Roman Catholic Church; depolonization and russification of educational-cultural space. It has been confirmed that the changing the policy to the Polish population on the Right-Bank territories in the 1830s fully corresponded to the strategic tasks of the imperial policy of centralization and unification in the sphere of state administration, in the legal and social-cultural space expressed in the ideologeme "autocracy, orthodoxy, people".